Influence of Long-Term Thinning on the Biomass Carbon and Soil Respiration in a Larch (Larix gmelinii) Forest in Northeastern China - Huimei Wang; Wei Liu; Wenjie Wang; Yuangang Zu (The Scientific World Journal)
Thinning management is used to improve timber production, but only a few data are available on how it influences ecosystem C sink capacity. This study aims to clarify the effects of thinning on C sinks of larch plantations, the most widespread forests in Northeastern China. Both C influx from biomass production and C efflux from each soil respiration component and its temperature sensitivity were determined for scaling-up ecosystem C sink estimation: microbial composition is measured for clarifying mechanism for respiratory changes from thinning treatment. Thinning management induced 6.23 mol C m−2 yr−1 increase in biomass C, while the decrease in heterotrophic respiration (Rh) at the thinned sites (0.9 mol C m−2 yr−1) has enhanced 14% of this biomass C increase. This decrease in Rh was a sum of the 42% decrease (4.1 mol C m−2 yr−1) in litter respiration and 3.2 mol C m−2 yr−1 more CO2 efflux from mineral soil in thinned sites compared with unthinned control. Increases in temperature, temperature sensitivity, alteration of litters, and microbial composition may be responsible for the contrary changes in Rh from mineral soil and litter respiration, respectively. These findings manifested that thinning management of larch plantations could enhance biomass accumulation and decrease respiratory efflux from soil, which resulted in the effectiveness improvement in sequestrating C in forest ecosystems.